MEASUREMENT OF THE INFLUENCE OF FACTORS ON THE IMPLEMENTATION OF ECOLOGICAL AND ECONOMIC ASSESSMENT OF URBANIZED TERRITORIES USING THE SWOT-ANALYSIS METHOD - KOBILINSKY, V. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Effective organic development of urban areas is one of the elements of ensuring a high quality of life. Changes in the environment lead to the formation of a new roadmap for transformation and urbanization, taking into account trends and patterns of phenomena that require detailed research, in particular, conducted on the basis of statistical research methods [1]. A particularly important task is to determine the system of indicators of urban environmental friendliness, study the relationship between them, study and evaluate the mechanisms of action of factors on phenomena. To date, there are no common approaches to determining the system of indicators that characterize the level of environmental pollution of cities and their environmental friendliness. And in the current assessments of indicators of socio-economic development of cities, environmental indicators in some respects are not fully taken into account, and in some are absent. In particular, this applies to methods of assessing the development of the territories of Ukraine (monitoring of regional development indicators) [2].It should be noted that the overall assessment of the ecological and economic condition of urban areas is quite complex, as it includes many areas that can not be determined by one indicator. Therefore, it is obvious that this should be a system of indicators that reflects the relationship between areas that occur under the influence of the natural environment. These indicators are closely interrelated with the processes of environmental protection of cities, are both its factors and results, which are reflected in direct dependence, the more measures are taken, the better the environmental situation in cities [3].The aim of the article is to conduct a SWOT analysis of the impact of factors on the implementation of environmental and economic assessment of urban areas, which indicates the existing strengths and weaknesses of these assessments, taking into account the impact of external and internal factors. According to the proposed situational analysis, the algorithm of SWOT-analysis was built and the results obtained were entered into the matrix, the available opportunities and threats were prioritized into three groups according to priority, the need to concentrate efforts and monitoring tools. The developed matrix of opportunities indicates favorable conditions and consequences that will lead to improved environmental and economic impact assessment of existing conglomerates. Thus, the application of SWOT-analysis in the assessment of impact results with the threats and opportunities presented in the work will optimize the use of available material, financial and labor resources to obtain full, scientifically sound, implemented to international standards evaluation results.
Keywords: SWOT-analysis; ecological and economic assessment; urbanized territories